Tissue Receptor for Cholera Exotoxin: Postulated Structure from Studies with G(M1) Ganglioside and Related Glycolipids - Holmgren, J. (1973)
By a double-diffusion precipitation-in-gel technique, isolated cholera toxin as well as its natural toxoid were shown to be fixed and precipitated by the ganglioside G(M1) but not by any of the related glycolipids G(M3), G(M2), G(M1)-GlcNAc, G(D1a), G(D1b), G(T1), globoside, G(A1), and tetrahexoside-GlcNAc. Twenty-five nanograms of G(M1) was enough to give a precipitation line with 1.2 μg of toxin, whereas about 50 ng was required with this amount of toxoid. G(M1) also inactivated the toxin in the ileal loop as well as in the intradermal models in rabbits. A 1: 1 molar ratio of ganglioside to toxin was found limiting, e.g., 100 pg of G(M1) could inactivate 5 ng (about 50 blueing doses) of isolated toxin. G(M1) inactivated crude toxin (culture fil rate) with the same efficiency as isolated toxin, and the inactivating capacity of G(M1) was unaffected by mixing with other gangliosides, indicating the specificity in the reaction between G(M1) and toxin. The other glycolipids tested did not inactivate toxin except G(D1a) and G(A1) which did so with approximately 1,000 times less efficiency than G(M1). This identified the portion Gal → GalNAc [Formula: see text] as the critical region in G(M1) for toxin fixation, and it is postulated that this may be the tissue receptor structure for the cholera toxin.